The complete ElfQuest Volume four - Pini, Wendy; Pini, Richard (Dark Horse Books, 2017)
"Weighing in at over six hundred pages, this collection presents ElfQuest: Hidden Years #10-15 and the complete Shards story arc (#1-16), along with a cover gallery with commentary from legendary creators Wendy and Richard Pini."--Page [4] of cover.